The non-linear influence of trade, foreign direct investment, financial development, energy supply and human capital on carbon emissions in the BRICS - Ganda, Fortune (Environmental science and pollution research international, 2021)
This research investigates the relationship between foreign direct investment, domestic credit to the private sector, energy supply and human capital on carbon emissions subject to the level of trade. In the interest of capturing this non-linear association, this paper utilises the fixed effect panel threshold model. Thus, deploying a panel dataset of BRICS economies from 2000 to 2018, the study produces important findings that trade exerts a considerable non-linear influence on environmental quality. In this context, the paper determines specific threshold levels upon which environmental quality either increase or decrease for the BRICS economies when either energy supply (1.5962, approximately $US 4.934 million), domestic credit to the private sector (1.6375, about $US 5.142 million), foreign direct investment (1.6375, about $US5.142 million) or human capital (1.6375, about $US5.142 million) increases. To ascertain the causation of included parameters, the Dumitrescu and Hurlin causality test results are also presented.